2016
DOI: 10.1021/acsami.5b11903
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Interfacial Reactions and Intermetallic Compound Growth at the Interface of a Lead-free Solder Joint with Layer-by-Layer Transferred Graphene

Abstract: The immoderate growth of intermetallic compounds (IMCs) formed at the interface of a solder metal and the substrate during soldering can degrade the mechanical properties and reliability of a solder joint in electronic packaging. Therefore, it is critical to control IMC growth at the solder joints between the solder and the substrate. In this study, we investigated the control of interfacial reactions and IMC growth by the layer-by-layer transfer of graphene during the reflow process at the interface between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…With increasing numbers of graphene layers, the contact angle of water on the copper surface gradually attains the value for water on the surface of graphite. In the most recent published work describing wetting of copper and copper covered by graphene with Sn-Ag-Cu (SAC) solder, 25 the authors describe the role of the graphene coating as a diffusion barrier, suggesting that the graphene layer should reduce copper diffusion from the substrate and thereby inhibit growth of the intermetallic layer. Cu atoms diffuse from the substrate through defects in the graphene coating.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing numbers of graphene layers, the contact angle of water on the copper surface gradually attains the value for water on the surface of graphite. In the most recent published work describing wetting of copper and copper covered by graphene with Sn-Ag-Cu (SAC) solder, 25 the authors describe the role of the graphene coating as a diffusion barrier, suggesting that the graphene layer should reduce copper diffusion from the substrate and thereby inhibit growth of the intermetallic layer. Cu atoms diffuse from the substrate through defects in the graphene coating.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, thermal solid state aging causes a transformation from existing low-temperature Cu 6 Sn 5 IMCs to existing high-temperature Cu 3 Sn IMCs [ 11 ]. Ko et al [ 83 ] indicated that Cu 3 Sn arises largely from the consumption of Cu 6 Sn 5 , as in Equation ( 3 ): …”
Section: Imcs Formationmentioning
confidence: 99%
“…Scanning electron microscopy (SEM; S-4700, Hitachi, Tokyo, Japan), together with energy dispersive X-ray spectroscopy (EDX; EDAX Genesis XM2 60, AMETEK, Mahwah, NJ, USA), was employed to characterize the IMC microstructure. For kinetic studies, the IMC thicknesses were measured from the SEM images of the metallographic cross-sections using the following image analysis procedure [7,8]: (1) an SEM image of each sample was obtained at the appropriate magnification; (2) the grayscale SEM image was enhanced using Adobe Photoshop (CS6, Adobe systems, San Jose, CA, USA, 2017) to identify the interfaces between the different layers; and (3) the mean thickness (H IMC ) of individual layers was calculated using the following equation:…”
Section: Characterization Of the Solder/cu Microstructurementioning
confidence: 99%
“…A 1% reduction of Ag in a solder alloy results in at least a 15% reduction of the total solder cost. Currently, commercial imperatives to reduce costs have raised considerable interest in lowering the Ag content of SAC solder alloys to reduce the base alloy cost, especially in the context of decreasing profits in electronics manufacturing due to intense competition [7][8][9]. In this context, Ag-free solders, specifically the eutectic SC07 solder, has attracted much attention in automotive electronic applications because of the low cost and good drop reliability.…”
Section: Introductionmentioning
confidence: 99%